Tool material effect on the friction stir butt welding of AA2124-T4 Alloy Matrix MMC - BOZKURT, YAHYA (ELSEVIER SCIENCE BV, 2018)
The purpose of the present work is to study on the effect of material properties tool on friction stir butt welding of AA2124-T4 alloy matrix MMC. Uncoated tool, coated tool with a CrN, and coated tool with AlTiN were used to weld aluminum MMC plates. Macrostructure and microstructure observations, ultimate tensile strength, wear resistance, and chemical analysis were carried out to determine the appropriate tool for joining these composite plates. Results showed that the good welded joints could be obtained when a tool is coated with AlTiN. (C) 2017 Brazilian Metallurgical, Materials and Mining Association. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: Friction stir welding; AA2124-T4 alloy matrix MMC; Tool wear; Tensile test; MECHANICAL-PROPERTIES; 6061+20-PERCENT AL2O3; MAGNESIUM ALLOY; ALUMINUM-ALLOYS; COMPOSITE; WEAR; MICROSTRUCTURE; OPTIMIZATION; PARAMETERS; BEHAVIOR